ON THE ELUSIVENESS OF CONTEXT. Issue 2 (May 2016) - SHOGIMEN, TAKASHI
ABSTRACT: How can we decide the pertinent context in which a given object of historical study should be examined? This question has long puzzled historians. In the field of intellectual history, the Cambridge contextual school represented by Quentin Skinner triggered a series of methodological debates, in part relating to its opaque notion of context; critics have argued that a satisfactory answer to the question—how to recover a relevant context—has yet to be given. This article tackles why the question has continued to elude us. The article demonstrates that it is simply impossible to propose a practical set of guidelines on how to reconstruct a correct context because the identification of the relevant context is presupposed in the logical structure of inference in historical inquiries; identifying a relevant context is logically antecedent to the inquiry. In order to show this, the article deploys Charles Sanders Peirce's theory of inference. Thus the article submits that Skinner conceptualized his method as what Peirce called "abduction, " which specifically seeks authorial intention as an explanatory hypothesis. This observation entails two ramifications in relation to the notion of context. One is that context in Skinner's methodology operates on two levels: heuristic and verificatory. Confusing the two functions of context has resulted in a futile debate over the difficulty of reconstructing context. The other ramification is that abduction always requires some sort of context in order to commence an inquiry, and that context is already known to the inquirer. Any attempt to reconstruct a context also requires yet another context to invoke, thus regressing into the search for relevant contexts ad infinitum . The elusiveness of context is thus inherent in the structure of our logical inference, which, according to Peirce, always begins with abduction.